PREVENTION OF ALLERGIES IN CHILDREN (American Journal of Pedagogical and Educational Research, 2023)
Over the past 30-40 years, the world has been a significant increase in the prevalence of IgE-mediated allergic diseases, including such as atopic dermatitis (AD), allergic rhinitis (AR) and bronchial asthma (BA), both among the adult population and among children. According to the European Allergy White Paper, today one in three European children suffers from allergies, and one in ten - asthma. This allowed the WHO in 1999 to include asthma and allergies as a priority for the next decade.